2022
DOI: 10.2217/fon-2022-0334
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Transformation to Acute Myeloid Leukemia in Patients With Higher-Risk Myelodysplastic Syndromes

Abstract: Aim: Forty percent of patients with higher-risk myelodysplastic syndromes (HR-MDS) transform to acute myeloid leukemia (AML). Materials & methods: This retrospective study assessed the impact of HR-MDS transformation to AML on OS in a 6-month landmark analysis and the results were validated using a time-varying analysis. Results: The rate of AML transformation was 26.9% at 1 year. Patients who transformed to AML had a higher risk of death than patients who did not in the 6-month landmark analysis (HR: 1.82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This finding is lower than that reported by Vamsi et al, who reported that AML transformation during a 1-year follow-up was 26.9% in higher-risk MDS patients, which were patients with intermediate IPSS-R prognostic risk or greater. 16 Another study with eight years of follow-up reported AML transformation in 13.9% of MDS patients, with a median of 5 (1-23) months. 35 It has been reported that approximately 10-35% of MDS cases evolve into acute leukemia during the disease course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is lower than that reported by Vamsi et al, who reported that AML transformation during a 1-year follow-up was 26.9% in higher-risk MDS patients, which were patients with intermediate IPSS-R prognostic risk or greater. 16 Another study with eight years of follow-up reported AML transformation in 13.9% of MDS patients, with a median of 5 (1-23) months. 35 It has been reported that approximately 10-35% of MDS cases evolve into acute leukemia during the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…15 Through the IPSS-R risk group, a clinician can differentiate patients with higher risk, with the treatment goals of delaying AML transformation and improving overall survival. 16 The current standard of management for high-risk patients includes hypomethylating agents, decitabine, azacitidine, and allogeneic stem cell transplants. 17 Cytogenetic abnormalities were abnormal in >50% of the patients at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 40% of patients with high-risk MDS can experience deterioration or evolution to AML [28,29]. Furthermore, MDS patients who progress to AML are at a higher risk of death than those who do not [30]. Therefore, it is vital to assess the impact of ADs on the rate of AML transformation in MDS patients as it may help to improve the survival of these patients.…”
Section: Impact Of Ads On the Rate Of Aml Transformationmentioning
confidence: 99%
“…2 The risk of progression to AML among patients with high-risk MDS is high (~40%). 3 MDS is an emerging disease in the elderly (the majority of patients are aged >70 years), 4 and due to an aging population in developing countries and the recent molecular advances in detecting clonality, the case-frequency of MDS is expected to increase over time with a high impact on health resources. 5,6 As MDS is mainly a disease of the elderly, comorbidities play an important role in the presentation and symptom burden of affected patients.…”
Section: Introductionmentioning
confidence: 99%